PEMBERDAYAAN MASYARAKAT PESISIR MELALUI TRADISI ANYAMAN PANDAN DI GAMPONG PEUNAGA RAYEUK KECAMATAN MEUREUBO KABUPATEN ACEH BARAT PROVINSI ACEH - Hayatun Nufus; M. Ali Sarong; Heriansyah Heriansyah; Asri Mursawal; Momamad Gazali (Jurnal Marine Kreatif, 2021)
The coastal area of Gampoeng Peunaga Raryeuk has a lot of potential for pandanus plants and is good for use as raw material for making pandanus woven. The people of Gampoeng Peunaga Rayeuk generally have weaving skills that have been passed down from generation to generation. However, so far the weaving activities have temporarily dimmed due to less varied product yields, thus affecting weak market power. In connection with the phenomenon in the field, training and community empowerment were carried out. The aim is to train people to make various plaits using pandan leaves that are around. This training activity uses demonstration and lecture methods. It is hoped that new jobs will be created, especially in the economic and agricultural fields for the people who live in Peunaga Rayek Village, Meureubo District, West Aceh Regency.